Event-triggered scheme for fault detection and isolation of non-linear system with time-varying delay - Aslam, Muhammad Shamrooz; Ullah, Rizwan; Dai, Xisheng; Sheng, Andong (IET control theory & applications, 2020)
In this article, we investigate a new way of dealing with fault detection and isolation (FDI) for a class of delayed non-linear systems with an event-triggered mechanism (ETM). This article is based on 1) To estimate the dynamics of the nonlinear plant, Sliding Mode Observers (SMO's) is manipulated with Luenberger. 2) Under the ETM, sampled data is released only when the plant's measurement (sampled) violate the specific threshold of the event condition. 3) First, transform into two subsystems. In subsystem-A contains uncertainties without sensor fault and vice-versa in subsystem-B. To handle the uncertainties that appeared in subsystem-A, a new SMO's implemented while traditional Luenberger is employed to detect the sensor fault. Then, by using a new Lyapunov-Krasovskii function approach performance index is proposed. Based on stability criteria, sufficient conditions are provided in the account of Linear Matrix Inequalities (LMIs). The simulation example is given to demonstrate the effectiveness of our design method.